2020
DOI: 10.3389/fonc.2020.01729
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Age at Diagnosis Upon Breast Cancer of Different Immunohistochemical Subtypes: A Surveillance, Epidemiology, and End Results (SEER) Population-Based Analysis

Abstract: Background and Objectives: The influence of age at diagnosis of breast cancer upon the prognosis of patients with different immunohistochemical (IHC)-defined subtypes is still incompletely defined. Our study aimed at examining the association of age at diagnosis and risk of breast cancer-specific mortality (BCSM). Methods: 172,179 eligible breast cancer patients were obtained for our study cohort using the Surveillance, Epidemiology, and End Results database from 2010 to 2015. Patients were classified into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
(69 reference statements)
4
15
0
1
Order By: Relevance
“…Additionally, some early-stage patients still have worse survival in clinical studies (2,3). A series of studies revealed that age, primary tumor size, tumor location, positive axillary lymph nodes, histological grade, molecular subtype, and BRCA mutation were closely correlated with the prognosis of breast cancer (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some early-stage patients still have worse survival in clinical studies (2,3). A series of studies revealed that age, primary tumor size, tumor location, positive axillary lymph nodes, histological grade, molecular subtype, and BRCA mutation were closely correlated with the prognosis of breast cancer (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The median age at diagnosis in our population of women with TN-PABC was 33.8 years (IQR 30.0e37.0) which was significantly lower than that of patients with TN-non-PABC (35.7 years; IQR 32.0e39.0). Previous studies have underlined that breast cancer diagnosed at a young age is correlated with lower survival rates and higher recurrence rates when compared with older patients [34,58,59]. Indeed, Liedtke et al found a significant correlation between age at diagnosis and overall survival, disease-free survival and distant disease-free survival in five age cohorts ( 30, 31e40, 41e50, 51e60 and >60 years) including 1732 patients with primary TNBC [58].…”
Section: Discussionmentioning
confidence: 99%
“…The median age at diagnosis in our population of women with TN-PABC was 33.8 years (IQR 30.0–37.0) which was significantly lower than that of patients with TN-non-PABC (35.7 years; IQR 32.0–39.0). Previous studies have underlined that breast cancer diagnosed at a young age is correlated with lower survival rates and higher recurrence rates when compared with older patients [ 34 , 58 , 59 ]. Indeed, Liedtke et al.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Recent well-controlled analyses have shown that the independent prognostic effect of young age is breast cancer subtype-specific and most evident in luminal-type breast cancers. [3][4][5] Luminal breast cancers express hormone receptors and thus are particularly susceptible to endocrine manipulations: adjuvant endocrine therapy or the chemo-endocrine effect of chemotherapy in premenopausal women. Although the prognostic value of chemotherapy-induced amenorrhea was acknowledged for many years, the role of ovarian ablation as a part of modern endocrine therapy for early breast cancers developing in premenopausal women has been long debated.…”
mentioning
confidence: 99%
“…Despite demonstrated improvements for women of all ages, young women (40 years old or younger at diagnosis) appear to remain at increased risk for breast cancer mortality in comparison with older women 2,3 . Recent well‐controlled analyses have shown that the independent prognostic effect of young age is breast cancer subtype–specific and most evident in luminal‐type breast cancers 3‐5 …”
mentioning
confidence: 99%